Bumblebee Behavior on Flowers, but Not Initial Attraction, Is Altered by Short-Term Drought Stress - Höfer, Rebecca J.; Ayasse, Manfred; Kuppler, Jonas (Frontiers in Plant Science, 2021)
Climate change is leading to increasing drought and higher temperatures, both of which reduce soil water levels and consequently water availability for plants. This reduction often induces physiological stress in plants, which in turn can affect floral development and production inducing phenotypic alterations in flowers. Because flower visitors notice and respond to small differences in floral phenotypes, changes in trait expression can alter trait-mediated flower visitor behavior. Temperature is also known to affect floral scent emission and foraging behavior and, therefore, might modulate trait-mediated flower visitor behavior. However, the link between changes in flower visitor behavior and floral traits in the context of increasing drought and temperature is still not fully understood. In a wind-tunnel experiment, we tested the behavior of 66 Bombus terrestris individuals in response to watered and drought-stressed Sinapis arvensis plants and determined whether these responses were modulated by air temperature. Further, we explored whether floral traits and drought treatment were correlated with bumblebee behavior. The initial attractiveness of drought and watered plants did not differ, as the time to first visit was similar. However, bumblebees visited watered plants more often, their visitation rate to flowers was higher on watered plants, and bumblebees stayed for longer, indicating that watered plants were more attractive for foraging. Bumblebee behavior differed between floral trait expressions, mostly independently of treatment, with larger inflorescences and flowers leading to a decrease in the time until the first flower visit and an increase in the number of visits and the flower visitation rate. Temperature modulated bumblebee activity, which was highest at 25 °C; the interaction of drought/water treatment and temperature led to higher visitation rate on watered plants at 20 °C, possibly as a result of higher nectar production. Thus, bumblebee behavior is influenced by the watered status of plants, and bumblebees can recognize differences in intraspecific phenotypes involving morphological traits and scent emission, despite overall morphological traits and scent emission not being clearly separated between treatments. Our results indicate that plants are able to buffer floral trait expressions against short-term drought events, potentially to maintain pollinator attraction.